Development of an Android-Based Smart Health Monitoring Device for Heartbeat Detection - Andi Zulherry; Muhammad Gunawan (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2025)
This research presents the development of a smart health monitoring system designed to detect and monitor heartbeat patterns using Android-based technology. The increasing prevalence of cardiovascular diseases necessitates accessible and user-friendly monitoring solutions for early detection and continuous health assessment. This study aims to design and implement a portable heartbeat detection device integrated with an Android application, enabling real-time monitoring and data analysis. The system utilizes pulse sensor technology to capture heartbeat signals, which are then processed by a microcontroller and transmitted wirelessly to an Android smartphone via Bluetooth connectivity. The developed application features an intuitive user interface that displays heart rate measurements, stores historical data, and provides alert notifications when abnormal patterns are detected. System testing was conducted to evaluate accuracy, reliability, and user experience across various conditions. Results demonstrate that the device achieves accurate heartbeat detection with minimal deviation from standard medical equipment, offering a practical and cost-effective solution for personal health monitoring. This research contributes to the advancement of mobile health (mHealth) technology, providing individuals with greater autonomy in managing their cardiovascular health while facilitating early intervention opportunities. The system's portability, affordability, and ease of use make it particularly suitable for home-based health monitoring and remote patient care applications.